(untitled) (Tempo e Argumento, 2023)
An important leader of the indigenous movement in the 1970s and 1980s, Mário Juruna was invited to represent the native peoples at the IV Russell Tribunal, to be held in Holland in 1980, whose purpose was to denounce and judge crimes committed against indigenous peoples in the Americas. Based on tutelary regime, the Funai and the Minister of the Interior Mário Andreazza denied authorization for Juruna to leave the country, claiming his inability to represent Brazil at that event. A frequent critic of the indigenist policy of the Brazilian Civil-Military Dictatorship, Mário Juruna spared no effort to confront this decision and filed a writ of mandamus at the Federal Court of Appeals against the Executive’s act. Based on this historical episode, in this article we analyze the arguments and attitudes of authorities in the Dictatorship based on tutelary power, reinforcing the thesis of coloniality as a structuring aspect of political and social relations in Brazil at the end of the 20th century. However, more than that, we highlight the leading role of the Xavante leadership Mário Juruna in the political clashes against the Brazilian government in order to contribute to the diachronic understanding of the historical mobilizations of original peoples in Brazil for recognition and autonomy.